Susceptibility to chlorantraniliprole, competition abilities and stylet probing behavior of heteropteran pests - Tuelher, Edmar de Souza (2017)
Large losses in agricultural production worldwide have occurred due to insects in the order Heteroptera. Records of severe losses in agricultural commodities [eg, soybean, Glycine max (L.)] in Brazil have been attributed to the action of a stink bug complex, whose main insect species have changed both spatially and temporally in soybean producing regions. More recently, other stink bug pests without occurrence in Brazil have been the main cause of crop losses with great relevance for Brazilian agricul- ture. Therefore, the present research was divided into three parts, aiming not only to address the current situation of two of the main pests in Brazilian soybean crops, the brown stink bug, Euschistus heros (F.), and the red banded stink bug, Piezodorus guildinii (West.), but also to provide relevant information about heteropteran pests in other countries and likely to become pests in Brazil, like Lygus lineolaris (Palisot de Beauvois). In the first study, the susceptibility of E. heros to the chlorantraniliprole insecticide was evaluated, as well as the alteration in the reproductive fitness medi- ated by sublethal exposure to this insecticide. The susceptibility of E. heros was eval- uated by assessing the mortality of newly emerged nymphs and adults. Alterations in reproductive fitness were evaluated by testing four combinations of treated and untreated couples: untreated male and treated female; treated male and untreated female; both male and female treated; both male and female untreated. Although chlorantraniliprole insecticide caused low mortality to E. heros during the develop- mental stages (3 rd , 4 th and 5 th instars and adults) treated, adults exposed to sublethal concentration of chlorantraniliprole had their reproductive fitness affected. There was an increase in survival time for untreated males coupled with treated females, and a higher oviposition peak for treated females coupled with untreated males, with shorter egg incubation time and delayed peak of fertility. Additionally, the untreated females coupled with treated males exhibited higher daily fecundity, potentially rep- resenting chlorantraniliprole-induced hormesis. In the second work, the competitive- ness of E. heros and P. guildinii was assessed by direct competition experiments with mixed (adult) insect infestations in soybean plants. Fitness of each species was mea- sured by quantifying the populational growth rate, and the soybean yield was ac- cessed at harvesting. The results showed that E. heros was a better competitor than P. guildinii, and the competitive ability of P. guildinii was compromised by the increase in the amount of conspecific and heterospecific (i.e., E. he ros). However, despite the fact that P. guildinii apparently lost the competition with E. heros, no yield was observed in the plants infested with P. guildinii. In the third work, the stylet probing behavior of L. lineolaris (Palisot de Beauvois) on cotton terminal axillary leaves was studied. L. lineolaris was chosen because it is a pest of great importance in several countries, but has not been recorded in Brazil. However, due to international trade there is a probability that this pest would become a problem if introduced in Brazil. The rela- tionship between characteristics of stylet probing behavior of L. lineolaris (3 rd , 4 th and 5 th instars and adult males) and the amount of leaf damage was analyzed. L. lineolaris stylet probing behavior was measured and quantitatively described by electropenet- rography (EPG). Cell rupturing (CR) events, composed of combined stylet movements and salivation during insect probing, are the main cause of damage on cotton axil- lary leaves. Strong correlation between total duration of CR with the amount of leaf damage was found. Differences between life stages and amount of damage on leaves were not found. Therefore, the CR feeding strategy was highly detrimental to leaves, even with low-duration events. These studies reinforce that the recent outbreaks and the higher abundance of E. heros observed in Brazilian soybean fields a re r elated to sublethal effects of chlorantraniliprole, and probably others insecticides, by altering the sexual fitness of E. heros, associated with its higher competitive ability against its heterospecific c ompetitor, P. g uildinii. A dditionally, E PG w ill b e a i mportant t ool to understand stylet probing behavior of soybean stink bugs pests. EPG application, in- cluding for studies with insecticides and their sublethal effects, will be a valuable tool to development of strategies to reduce soybean crop lost.